Art et ordinateur. - Moles, Abraham A. (Paris : Blusson Editeur, 1990)
Marcus, Aaron ; Roy, John ; Yamanaka), CTG (Komura & ; Nees, Georg ; Lecci, Auro ; Nake, Frieder ; Vasarely, Victor ; Francke, Herbert W. ; Molnar, Vera ; Mohr, Manfred ; Ridell, Torsten ; Knowlton, Ken ; Swartz, Lilian ; Colonna, Jean François ; Norton, Alan ; Wender, Monique ; de Senneville, Elisabeth ; Colonna, J-F ; Schwarz, Lilian ; Vasulka, Steina & Woody ; Latham, William ; Höhne, K.H. ; NCSA (University of Illinois) ; Cirad ; Kawaguchi, Yiochiro ; Hill, G. ; Sims, Karl ; Logue, John ; Paik, Nam June ; Renault ; Oliver, Vaughan ; Fukomoto, Omura
Bibliografie, Filmografie
Frans
boek